Research on the key problems of MPPT strategy based on active power control of hydraulic wind turbines - Ai, Chao; Bai, Wenjie; Zhang, Tingyuan; Kong, Xiangdong (Journal of renewable and sustainable energy, 2019)
The constant displacement pump-variable motor hydrostatic transmission system is used as the main drive system in hydraulic wind turbines, and unlike traditional wind turbines using asynchronous generators and electronic converter devices, the synchronous generator is directly adopted for grid-connected generation. In this paper, the maximum power point tracking (MPPT) problem of hydraulic wind turbines is studied in depth. The energy transfer process of hydraulic wind turbines is introduced, and the key issues to be solved in MPPT are presented. A MPPT strategy based on active power control is proposed. The power transmission characteristics of hydraulic wind turbines and the nonlinear problems existing in active power control are analyzed. A small signal linearization method combined with variable gain proportional integral differentiation (PID) is used to solve the power response inconsistent problems that come from system nonlinearity. The MPPT strategy based on active power control is optimized by a speed control loop to insure the system stability in the process of MPPT. Finally, the power response consistency and the MPPT strategy are verified in the 30 kVA semi physical simulation platform.